An introduction to the design and behavior of bolted joints - Bickford, John H. (Mechanical engineering (Marcel Dekker, Inc.), 1995)
Offering a broad-based review of the factors affecting the design, assembly and behaviour of bolted joints and their components in all industries, this work details various assembly options as well as specific failure modes and strategies for their avoidance. This edition features material on: the contact stresses between bolt head or nut face and the joint; thread forms, series and classes; the stiffness of raised face flange joints; and more.